2021
DOI: 10.1002/cyto.a.24489
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in plasmonic nanoparticle‐based biomarker detection and cytometry for the study of central nervous system disorders

Abstract: Neurological disorders affect hundreds of millions of people around the world, are often life-threatening, untreatable, and can result in debilitating symptoms. The high prevalence of these disorders, which feature biochemical or structural abnormalities in neuronal systems, has spurned innovations in both rapid and early detection to assist in the selection of appropriate treatment strategies to improve the patients' quality of life. Plasmonic nanoparticles (PNPs), a versatile and promising class of nanomater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…Ubiquitin-C-terminal hydrolase-L1 (UCH-L1) plasma limits have been found to be significantly higher in TBI patients than in healthy people, implying that UCH-L1 could be a viable diagnostic marker for the situation [42]. An innovative technique based on the surface plasmon resonance of Au NPs has recently been shown to successfully and swiftly identify the biomarker UCH-L1 in TBI patients with 100% sensitivity and specificity [43].…”
Section: Biomarker Detectionmentioning
confidence: 99%
“…Ubiquitin-C-terminal hydrolase-L1 (UCH-L1) plasma limits have been found to be significantly higher in TBI patients than in healthy people, implying that UCH-L1 could be a viable diagnostic marker for the situation [42]. An innovative technique based on the surface plasmon resonance of Au NPs has recently been shown to successfully and swiftly identify the biomarker UCH-L1 in TBI patients with 100% sensitivity and specificity [43].…”
Section: Biomarker Detectionmentioning
confidence: 99%
“…However, the complexities of the CNS provide significant hurdles to the analysis done by this equipment on many biomarkers. [23] Essentially, bio-sensing equipment are designed to convert biological or chemical events into countable signals that provide quantitative and/or qualitative information about the sought -after biomarkers. [24] Biosensors are normally comprised of the detector, which confirms the impetus; the transducer, which converts the impetus to a valuable consequence; and the signal handling technique, which displays the results in a suitable and legible style, [10] as illustrated in Figure 2.…”
Section: Recent Developments In Widespread Neurological Disordersmentioning
confidence: 99%
“…[ 3 ] However, it has been found that a certain enzyme that has been implicated in a range of neurological disorders may serve as a biomarker. [ 4–6 ]…”
Section: Introductionmentioning
confidence: 99%